UVA/persulfate-driven nonylphenol polyethoxylate degradation: effect of process conditions. Issue 2 (15th January 2022) - Nunes, R. F.; Tominaga, F. K.; Borrely, S. I.; Teixeira, A. C. S. C.
ABSTRACT: UV/persulfate (UV/PS) technologies have gained increased attention as efficient alternatives for removing pollutants from different classes, although processes based on the UVA-driven S 2 O 8 2 − (PS) activation have not yet been discussed in the literature for the removal of the nonionic surfactant nonylphenol polyethoxylate (NPEO). The present study investigated the simultaneous effect of the initial persulfate concentration ([PS]0 ) and specific photon emission rate ( E P, 0 ) on NPEO degradation by UVA/PS following a Doehlert experimental design. The results for [NPEO]0 = (4.65 ± 0.15) mg L −1 indicated more than 97.8% NPEO removal after 2 h, with pseudo first-order specific degradation rate ( k obs ) of 0.0320 min −1, for [PS]0 = 7.75 mmol L −1 and E P, 0 = 0.437 μmol photons L −1 s −1 . Under these conditions, NPEO half-life time was about 22 min, and the EC50 -48 h (% v/v) values for Daphnia similis before and after treatment did not differ significantly. Higher values of E P, 0 would influence NPEO removal for [PS]0 not higher than 8–10 mmol L −1, although lower degradation efficiencies were obtained with higher [NPEO]0 or real wastewater, except for longer reaction times. Additionally, UVA/PS showed to be efficient for tensoactivity removal, despite the negligible total organic carbon (TOC) removal achieved. Finally, UVC and UVA resulted in NPEO degradation higher than 96% and similar tensoactivity removals when UVA/PS was conducted under optimal conditions ([PS]0 = 10 mmol L −1 ; E P, 0 = 0.324 μmol photons L −1 s −1 ), suggesting that UVA radiation available in solar light could be advantageously employed for NPEO removal at concentrations usually found in wastewater. GRAPHICAL ABSTRACT: UF0001